My Neighbour: the Good Samaritan (Luke 10,25–37) and the Theory of Recognition - Falcetta, Alessandro (Biblische Zeitschrift, 2026)
The question introducing the parable of the Good Samaritan, "Who is my neighbour?" can be interpreted as a question about recognition. This serves as the starting point for exploring whether Luke 10:25-37 can be read in light of the theory of recognition as formulated by philosopher Axel Honneth. This approach has already been applied to the Hebrew Bible by Bernd Janowski and to the New Testament by other scholars. Our exploration suggests that numerous interpretative challenges in the Good Samaritan pericope can be understood as issues of recognition. The recognition paradigm allows us to view the story as a coherent text that expresses motifs and themes which have only in modern times been systematized in philosophical theory. Furthermore, the parable may contribute to the theory of recognition by supporting the proposal made by some scholars that recognition should be unconditional.